2013 International Conference on Renewable Energy Research and Applications (ICRERA) 2013
DOI: 10.1109/icrera.2013.6749923
|View full text |Cite
|
Sign up to set email alerts
|

On the harvest of rainfall energy by means of piezoelectric transducer

Abstract: In this paper a detailed study on the harvest of the energy contained in rainfall by means of piezoelectric transducers is presented. Diverse studies agree on the level of suitable generated voltage on the electrodes of a piezoelectric transducer subjected to rainfall, but a complete characterization on the supplied power is still missing. This work, in order to limit optimistic forecasts, takes into account the behavior of the transducers subjected to real and also artificial rainfall, condition that has show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The current change during T on2 is given by: (5) M L '2 = m2Ton2 (6) Between Toni and Ton2 a dead time is introduced where both MOSI and MOS2 are switched-off to avoid cross conduction. The circuit configuration during the dead-time is the same of the off time and therefore the dead time is included in TalI subinterval.…”
Section: �= Lmentioning
confidence: 99%
See 1 more Smart Citation
“…The current change during T on2 is given by: (5) M L '2 = m2Ton2 (6) Between Toni and Ton2 a dead time is introduced where both MOSI and MOS2 are switched-off to avoid cross conduction. The circuit configuration during the dead-time is the same of the off time and therefore the dead time is included in TalI subinterval.…”
Section: �= Lmentioning
confidence: 99%
“…Solar, wind, hydrogen sources are widely promoted for stationary, low power and vehicular applications [1][2][3][4][5][6]. Hybrid energy systems, including renewable and conventional sources, have received a great deal of attention in the last decade to achieve reliable and environmentally friendly supplies.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Fig. 2 shows the two models locked in one end (Viola et al, [13][14][15][16][17][18]) and two ends (Jager et al, [5][6]). Larger collection surfaces can be used, made with piezoelectric material (Perera et al, [26]), or with an inert collecting diaphragm linked to piezoelectric cantilevers (Wong Ching-Hong et al [27]), as shown in Fig.…”
Section: Piezoelectric Transducers and Raindropmentioning
confidence: 99%
“…Roundy [12] proposed useful schemes for the modeling of the electromechanical coupling and these models are here validated for the raindrop harvester. The French studies [5][6] have demonstrated that a single raindrop with diameters ranging between 1 and 5 mm can generate up to 12mJ/s, whereas Italian studies have shown that the piezoelectric transducer-based conversion system produces 0.43 µJ of energy for each raindrop that impacts it [13][14][15][16][17][18]. A recent work of Helseth [19] introduces different possibilities to harvest raindrop energy with piezoelectric and triboelectric transducers and evaluates the energy potential due to rain parameters.…”
Section: Introductionmentioning
confidence: 99%
“…For larger surfaces, hitted by random pulses, approaches based on the theory of random vibrations proposed in [33,34] can facilitate the raindrop energy harvesting. Matched inductive loads and schemes, which place a capacitor before the load in the conditioning circuit [35,36], increase the electrical energy transferred to the electrical system. A more definite analysis will concern the behavior of the device in the presence of strong stresses in terms of the electromagnetic field [37][38][39], by modeling the device as a receiving antenna [40][41][42] or in advanced interconnected configurations [43].…”
Section: Introductionmentioning
confidence: 99%